一种实时决策支持的智能变尺度数据分析方法及系统 (2023)
本发明提供了一种实时决策支持的智能变尺度数据分析方法及系统，涉及智能数据分析技术领域。包括通过思维概念图中的"概念对"得到思维序列，计算思维序列相似性，利用相似性结果聚集思维序列形成分析问题；计算分析问题相似性，聚集相似分析问题，识别思维主题图中的分析主题。根据不同数据分析任务的结构形态特征，确定各分析主题包含的数据分析任务。建立多尺度数据模型。根据数据分析任务判定结果，匹配元数据分析算法，对多尺度数据模型进行变尺度数据分析。本发明解决了分析主题发现、数据分析任务判定、数据分析层次转换等智能决策技术问题，提升了数据分析任务判定的准确率和效率，实现了对跨行业管理决策场景的实时决策支持。 The invention provides an intelligent variable-scale data analysis method and system supported by real-time decision, and relates to the technical field of intelligent data analysis. Comprising the steps of obtaining thinking sequences through concept pairs in a thinking concept graph, calculating thinking sequence similarity, and aggregating the thinking sequences by utilizing similarity results to form an analysis problem; and calculating and analyzing problem similarity, gathering similar analysis problems, and identifying an analysis topic in the thinking topic map. And determining the data analysis tasks contained in the analysis subjects according to the structural morphological characteristics of different data